PENERAPAN METODE ROLE PLAYING (BERMAIN PERAN) UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS IV SDN 24 BANDA ACEH - Ika Ramasari; Wahidah Nasution; Teuku Mahmud (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve students' speaking skills in Indonesian language subjects through the application of the Role Playing method on the "Interview" material. This study was conducted in class IVd SDN 24 Banda Aceh. The type of research used is Classroom Action Research (PTK) which is carried out in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. Data collection techniques in this study used a speaking skills test in the form of performance assessment with an assessment rubric, observation of learning activities and documentation of learning activities. Data were analyzed quantitatively and qualitatively. The results showed that the average value of students' speaking skills increased from Cycle I to Cycle II. In Cycle I, the average value of students' speaking skills was 72.36 with a completion percentage of 57.57%. In Cycle II, the average value increased to 80.63% with a completion percentage of 87.87%. Based on these results, it can be concluded that the application of the Role Playing method can improve students' speaking skills in Indonesian language subjects in class IV SDN 24 Banda Aceh.